Boosting CO2 electroreduction by iodine-treated porous nitrogen-doped carbon. (November 2020) - Feng, Jiaqi; Zeng, Shaojuan; Jiang, Chongyang; Dong, Haifeng; Liu, Licheng; Zhang, Xiangping
Graphical abstract: Highlights: The porous N doped-carbon was synthesized by pyrolysis of I2 treated-polyaniline. The porous N doped-carbon showed superior performance after the I2 treatment. The I2 treatment enhanced both the surface area and the pyrrolic N content. A detailed study indicated that the pyrrolic N served as the active site. Abstract: Electrochemical carbon dioxide reduction reaction (CO2 RR) provides a promising pathway for both decreasing atmospheric CO2 concentration and producing valuable carbon-based fuels. Exploring efficient and lower cost catalysts for CO2 RR is of great importance, but still remains challenging. Herein, the iodine-treated porous N-doped carbon is fabricated as an efficient metal-free catalyst for CO2 electroreduction. The catalyst exhibits nearly 100% CO Faradaic efficiency with partial CO current density of 38.2 mA cm −2 at a low overpotential in ionic liquid electrolyte. A detailed study indicates that the pyrrolic N serves as the active site for CO formation. The iodine treatment not only enhances the electrochemical active surface area and decreases the interfacial charge-transfer resistance of the catalyst, but also increases the content of pyrrolic N that is confirmed as active site. This work presents an efficient strategy to explore highly efficient metal-free electrocatalyst for CO2 RR, which has great application potentials.